Unofficial Media, Government Trust, and System Confidence Evidence From China: An Empirical Exploration of the Attitudes of Netizens Based on the Dual Moderating Effect - Chen, Caijuan; Li, Li; Ye, Jie (Frontiers in Psychology, 2022)
Abstract: Mass media has a significant effect on public support for the government. This paper constructs a mixed model with official media use as the moderating variable and government trust as the intermediary variable to explore the mechanism of unofficial media use affects system confidence, using data from a survey of political and social attitude of netizens (2015). The study finds that official media use weakens the negative role of unofficial media use in building system confidence, with the intermediary variable of government trust creating the necessary conditions for weakening the effect of official media use. The effect of unofficial media use on system confidence is heterogeneous. These findings remind us that it is necessary to deepen research into the micro-mechanisms that explain how unofficial media use reduce system confidence, a task for which cognitive theory is well suited.